Influence of crystallinity and chain interactions on the electrical properties of polyamides/carbon nanotubes nanocomposites - Hamester M.R.R.* (2021)
© 2021 Wiley Periodicals LLC.This work evaluates the effects of the crystallinity degree and π–π interactions between nanoparticles and a polymeric matrix on the electrical properties of polyamides and carbon nanotubes (CNT) nanocomposites. Two polymeric matrices were chosen; polyamide (PA) 6.6, a semi-crystalline polymer, and PA 6I-6T (here called aPA), a semi-aromatic and amorphous polyamide. The PA 6.6 crystallinity degree did not significantly change. Both lamellar thicknesses, amorphous (La) and crystalline (Lc), were estimated through Small-angle X-ray scattering. La increased significantly when CNTs were added. Both nanocomposites presented almost the same percolation threshold. In aPA nanocomposites, the π–π interaction between aromatic groups of CNTs and aPA is not only responsible for a homogeneous CNT dispersion, but also creates a direct path, parallel to the electrodes, for electron conduction after the percolation limit. In the PA 6.6 nanocomposites, the CNTs preferably disperse in the amorphous regions, forming a conductive network.